Pengaruh capital inflow terhadap pertumbuhan ekonomi di Indonesia periode 2001-2012 - Zulkarnain, Arif; Mayes, Anthony; Kornita, Sri Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The global financial crisis that occurred at the end of 2008 have an impact on the world economy in 2009. The crisis is caused by a number of large financial institutions experiencing financial difficulties as in the USA, Europe and so on. Due to the high risk of investing in countries in crisis, then investors more confidence to invest in emerging markets countries. The purpose of this study was to observe the effect of capital inflows on economic growth in Indonesia 2001-2012 period. This study uses annual time series data from Indonesian Central Banks (BI) and the central statistical burue (BPS). The model used in this study was a simple linear regression method. The conclusion is the regression of the gross domestic product (GDP), foreign direct investment (FDI) and portfolio investment (PI) have a positive and significant on GDP. The magnitude of the effect that the (R2) FDI is 96% and the rest is explained by other factors outside the model. While PI of 92,4% and the rest is explained by other factors outside the model. The regression result previously FDI and PI previous year to economic growth, show that both have a positive effect on economic growth in Indonesia during the period of study. The magnitude of the effect that the (R2) FDI the previous year was 47,9% and the rest is explained by other factor soutside the model. While the effect of PI previous year amounted to 59.7% and the rest is influenced by other factors outside the model.Keywords : Capital inflow, Gross domestic product (GDP), economic growth.